Meld Criteria in the Transplant Waiting List: Impact on Mortality Overall and by Diagnostic Groups - Ribeiro Melki, Caio (2022)
The modification of liver graft allocation for selection by severity criteria based on the Model for End-Stage Liver Disease (Meld) has not yet been properly analyzed in Brazil regarding the distribution of indications for transplant and mortality among enrolled patients. In a context of low organ donation and procurement, this assessment is relevant. Objective: To compare mortality on the liver transplant waiting list in Brazil before and after the adoption of Meld score as a criterion for allocation on the waiting list: overall, by diagnostic group, and by Meld range at enrollment. Methods: We retrospectively studied 899 patients (median age = 52.8 years, body mass index, BMI = 25.2 and Meld = 18) divided into the pre- (n = 320, 35.6%) and post-Meld (n = 579, 64.4%) periods and into groups: 1 (n = 480, 53.4%): ethanolic, cryptogenic and autoimmune cirrhosis; 2 (n = 80, 8.9%): biliary diseases; 3 (n = 93, 10.3%): metabolic and other diseases; and 4 (n = 246, 27.4%): post-viral B and C cirrhosis. Special scoring was assigned to 19.5% of patients, according to legislation criteria. The sample was also divided by Meld ranges at enrollment (< 18; 18–24; and > 24). Waitlist mortalities of the pre- and post-Meld groups were compared in the total sample, in each diagnostic group, and in each Meld range. Results: The incidence of referrals to transplantation was different in the pre- and post-Meld eras (p = 0.049), increasing in group 3 (from 8.1 to 11.6%) and decreasing in group 4 (from 32.5 to 24.5%). Of the enrollees, 32.9% died before transplantation. Mean Meld increased from 16 to 20 (p < 0.001), and mean time between enrollment and outcome (transplant or death) decreased from 102 days to 58 (p = 0.028). Waiting list mortality dropped from 105.7% (patient-years) to 54.9% in the post-Meld group (p = 0.001). There was a reduction from 104.2% (patientyears) to 51.1% (p = 0.034) in group 1, and the proportion fell from 160.3% (patient-years) to 52% (p = 0.019) in group 2. On the other hand, there was no statistically significant variation in the groups 3 and 4. In Meld range 1 (< 18), mortality ranged from 87.2% per patient-year to 24.1% per patientyear (p = 0.005). In Meld range 2 (18–24), it ranged from 109.8 to 72.4% per patient-year (p = 0.019). In the Meld > 24 range, there was no significant change in waitlist mortality. Finally, survival at 1, 3 and 12  months after transplantation did not vary significantly between the pre-Meld and postMeld era. Conclusion: Comparing the pre- and post-Meld groups, patients were enrolled when they were most severely ill, and there was a reduction in mean time on the list for the outcome and a decrease in waiting list mortality with no change in post-transplant survival. Diagnosis groups 1 and 2 have benefited. In addition, the decrease in waiting list mortality was observed among patients with Meld < 24 at the time of enrollment. This reduction was not observed in the group of patients with Meld > 24